Mengenali Keterlambatan Bicara dan Bahasa pada Anak - Nurul Razoki Yonianda Panjaitan; Ade Saifan Surya (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Speech and language are often mistaken to be synonymous. Speech is the articulation and production of speech sounds within the mouth, whereas language encompasses comprehension, processing and production of communication. Speech delay can be caused by hearing loss, brain disorders (such as mental retardation, specific receptive and/or expressive language disorders), autism, or disorders of the oral organs that make it difficult for a child to pronounce words (known as articulation disorders). To diagnose the cause of speech delay, a thorough examination by a doctor is necessary, which sometimes requires a multidisciplinary approach involving a pediatrician, an ENT specialist, and a child psychologist or psychiatrist. The developmental and growth stages are sensitive periods in a child’s life. This term “sensitive period” is a more nuanced way of referring to the critical periods in a child’s growth and development. Language disorders, particularly speech delay, are a common developmental issue. Several studies in various countries indicate that approximately 6 to 8% of preschoolers have speech delay. Early detection and intervention can improve emotional, social, and cognitive functioning, thereby improving outcomes. If a speech delay is suspected in a child, parents should be informed, and the child should be referred immediately to a speech-language pathologist and an audiologist.